Predictors of Acute Postsurgical Pain following Gastrointestinal Surgery: A Prospective Cohort Study - Qing-Ren Liu; Mu-Huo Ji; Yu-Chen Dai; Xing-Bing Sun; Cheng-Mao Zhou; Xiao-Dong Qiu; Jian-Jun Yang (Pain Research and Management)
Background. Several predictors have been shown to be independently associated with chronic postsurgical pain for gastrointestinal surgery, but few studies have investigated the factors associated with acute postsurgical pain (APSP). The aim of this study was to identify the predictors of APSP intensity and severity through investigating demographic, psychological, and clinical variables. Methods. We performed a prospective cohort study of 282 patients undergoing gastrointestinal surgery to analyze the predictors of APSP. Psychological questionnaires were assessed 1 day before surgery. Meanwhile, demographic characteristics and perioperative data were collected. The primary outcomes are APSP intensity assessed by numeric rating scale (NRS) and APSP severity defined as a clinically meaningful pain when NRS ≥4. The predictors for APSP intensity and severity were determined using multiple linear regression and multivariate logistic regression, respectively. Results. 112 patients (39.7%) reported a clinically meaningful pain during the first 24 hours postoperatively. Oral morphine milligram equivalent (MME) consumption (β 0.05, 95% CI 0.03–0.07, p<0.001), preoperative anxiety (β 0.12, 95% CI 0.08–0.15, p<0.001), and expected postsurgical pain intensity (β 0.12, 95% CI 0.06–0.18, p<0.001) were positively associated with APSP intensity. Furthermore, MME consumption (OR 1.15, 95% CI 1.10–1.21, p<0.001), preoperative anxiety (OR 1.33, 95% CI 1.21–1.46, p<0.001), and expected postsurgical pain intensity (OR 1.36, 95% CI 1.17–1.57, p<0.001) were independently associated with APSP severity. Conclusion. These results suggested that the predictors for APSP intensity following gastrointestinal surgery included analgesic consumption, preoperative anxiety, and expected postsurgical pain, which were also the risk factors for APSP severity.